Taxonomic revision of the Afrotropical bee genus Serapista Cockerell (Hymenoptera: Apoidea: Megachilidae: Megachilinae: Anthidiini) - Eardley, Connal; Griswold, Terry (Zootaxa, 2016)
The Sub-Saharan bee genus Serapista Cockerell is revised. It comprises six species. Serapista pernigra Cockerell is restored as a valid species, S. aspernigra Eardley and Griswold, new species, is described from the eastern part of southern Africa and Serapista rhodesiana Mavromoustakis is synonymized with S. pernigra. Descriptions, keys for identification, distributional records and floral associations of the species of Serapista are given.